2019
DOI: 10.18203/2349-3291.ijcp20190732
|View full text |Cite
|
Sign up to set email alerts
|

Clinico-bacteriological profile of neonatal sepsis

Abstract: Background: Neonatal sepsis is the commonest cause of neonatal mortality responsible for about 30-50% of total neonatal deaths in developing countries. Surveillance of causative organisms and their antibiotic sensitivity pattern promotes rational use of antibiotics and antibiotic stewardship.Methods: A retrospective study, relevant data regarding the neonates diagnosed with culture positive sepsis was obtained from the case records during the period from July 2014 to June 2017. Culture positive sepsis was defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…Our finding that the majority (67.5%, 27/40) of the isolates were gram-positive is in line with previous reports from Ethiopia [3,23], Nepal [12], India [24][25], Egypt [22], and Vietnam [26]. On the other hand, several studies have also reported the reverse (a dominant pattern of gram-negative neonatal sepsis) [22,[27][28][29][30][31][32][33].…”
Section: Discussionsupporting
confidence: 93%
“…Our finding that the majority (67.5%, 27/40) of the isolates were gram-positive is in line with previous reports from Ethiopia [3,23], Nepal [12], India [24][25], Egypt [22], and Vietnam [26]. On the other hand, several studies have also reported the reverse (a dominant pattern of gram-negative neonatal sepsis) [22,[27][28][29][30][31][32][33].…”
Section: Discussionsupporting
confidence: 93%
“…Other previous studies included neonates with late onset sepsis caused by grampositive and gram-negative organisms. [13][14][15] Most common isolated organism in the study was the Klebsiella spp. This finding is in accordance with those of the previously published studies which reported Klebsiella spp.…”
Section: Discussionmentioning
confidence: 99%
“…Other previous studies included neonates with late onset sepsis caused by gram-positive and gram-negative organisms. 13 - 15…”
Section: Discussionmentioning
confidence: 99%